Clinical differences between early- and late-onset psoriasis in Thai patients - Leena Chularojanamontri (2018)
© 2014 The International Society of Dermatology. Objectives: There is a paucity of data regarding clinical differences between early-onset psoriasis (EOP) and late-onset psoriasis (LOP) in Asian populations. This study aimed to investigate clinical differences between EOP (onset at the age of <40 years) and LOP (onset at the age of ≥40 years) in Thai patients. Methods: From 2002 until 2008, staff and residents in the Department of Dermatology, Siriraj Hospital, were asked to complete a questionnaire detailing the age of onset, family history of psoriasis, comorbid diseases, clinical features, nail and joint involvement, and severity of psoriasis in all psoriasis patients. Data were analyzed using descriptive statistics and chi-squared tests. Results: A total of 1017 patients were enrolled. Of these, 663 (65.2%) patients had EOP and 354 (34.8%) had LOP. The mean ± standard deviation age of onset was 24.8 ± 8.7 years in the EOP group and 51.6 ± 9.6 years in the LOP group. The two most common comorbid diseases were hypertension and diabetes mellitus in both groups. Patients with EOP had a significantly higher likelihood of both a family history of disease and guttate psoriasis. Palmoplantar psoriasis was more commonly found in LOP patients. Nail and joint involvement and disease severity were not associated significantly with age of onset. Conclusions: The present study supports the hypothesis that there are clinical differences between EOP and LOP in Asian populations.